2016
DOI: 10.3171/2015.10.jns1591
|View full text |Cite
|
Sign up to set email alerts
|

Chronic spatial working memory deficit associated with the superior longitudinal fasciculus: a study using voxel-based lesion-symptom mapping and intraoperative direct stimulation in right prefrontal glioma surgery

Abstract: OBJECTIVE Although the right prefrontal region is regarded as a silent area, chronic deficits of the executive function, including working memory (WM), could occur after resection of a right prefrontal glioma. This may be overlooked by postoperative standard examinations, and the disabilities could affect the patient's professional life. The right prefrontal region is a part of the frontoparietal network and is subserved by the superior longitudinal fasciculus (SLF); however, the role of the SLF in spatial WM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 45 publications
1
40
0
3
Order By: Relevance
“…FAT расположен по задней границе опухоли и тесно прилежит к ней; д -интраоперационное фото: 0, 2, 3, 41 -зоны нарушений речи в ложе раны, полученные при прямой электрической стимуляции; обращает на себя внимание топография выявленных зон, соответствующая ходу волокон FAT; е -МРТ после операции в первые 72 ч. Стрелкой обозначена гемостатическая метка (оставленный в полости ложа по заднему контуру опухоли фрагмент гемостатической марли в зоне найденных при электрической стимуляции речевых нарушений), ж -послеоперационная МР-трактография: желтым цветом обозначен AF, синим -FAT, зеленым цветом выделены остатки опухоли. ционного исследования у больных с эпилепсией или опухолями головного мозга, подкорковые волокна таким способом оценить нелегко [22].…”
Section: Discussionunclassified
“…FAT расположен по задней границе опухоли и тесно прилежит к ней; д -интраоперационное фото: 0, 2, 3, 41 -зоны нарушений речи в ложе раны, полученные при прямой электрической стимуляции; обращает на себя внимание топография выявленных зон, соответствующая ходу волокон FAT; е -МРТ после операции в первые 72 ч. Стрелкой обозначена гемостатическая метка (оставленный в полости ложа по заднему контуру опухоли фрагмент гемостатической марли в зоне найденных при электрической стимуляции речевых нарушений), ж -послеоперационная МР-трактография: желтым цветом обозначен AF, синим -FAT, зеленым цветом выделены остатки опухоли. ционного исследования у больных с эпилепсией или опухолями головного мозга, подкорковые волокна таким способом оценить нелегко [22].…”
Section: Discussionunclassified
“…Neuroimaging studies have implicated the frontal and posterior parietal cortices in working memory . This coordination is likely supported by the SLF, and several studies have demonstrated a relationship between the SLF and working memory . A DTI study of individuals with Gulf War illness showed a correlation between abnormality of the right SLF and fatigue .…”
Section: Discussionmentioning
confidence: 99%
“…28,29 This coordination is likely supported by the SLF, and several studies have demonstrated a relationship between the SLF and working memory. 30,31 A DTI study of individuals with Gulf War illness showed a correlation between abnormality of the right SLF and fatigue. 32 Thus, dysfunction in the right SLF may underlie some of the core affective symptoms seen in ME/CFS.…”
Section: Discussionmentioning
confidence: 99%
“…21,37) Our previous study suggested that spatial working memory would be performed via parieto-frontal networks, especially with the right SLF I and II, damage to which caused chronic impairment of this function. 38) …”
Section: White Matter Tracts and Dessmentioning
confidence: 99%